Like life : sculpture, color, and the body - Syson, Luke; Wagstaff, Sheena; Bowyer, Emerson; Kumar, Brinda; Kher, Bharti, 1969-; Metropolitan Museum of Art (New York, N.Y.) (New York : The Metropolitan Museum of Art, 2018)
Since the earliest myths of the sculptor Pygmalion bringing a statue to life through desire, artists have explored the boundaries between sculpture and the physical materiality of the body. This groundbreaking volume examines key sculptural works from 13th-century Europe to the global present, revealing new insights into the strategies artists deploy to blur the distinction between art and life. Sculpture, which has historically taken the human figure as its subject, is presented here in myriad manifestations created by artists ranging from Donatello and Degas to Picasso, Kiki Smith, and Jeff Koons. Featuring works created in traditional media such as wood and marble as well as the unexpected such as wax, metal, and blood, Like Life presents sculpture both conventional and shocking, including effigies, dolls, mannequins, automata, waxworks, and anatomical models. Containing texts by art and cultural historians as well as interviews with contemporary artists, this is a provocative exploration of three-dimensional representations of the human body.
Embodied Histories / Sheena Wagstaff -- Polychrome and Its Discontents: A History / Luke Syson -- No Dead Matter / Marina Warner -- Double or Nothing / Hillel Schwartz -- Material Histories. Bharti Kher: The Sensuality of Impermanence -- Alison Saar: Material Wisdom -- Fred Wilson: Object Histories -- Jeff Koons: Democratizing Material -- The Presumption of White / Emerson Bowyer -- Likeness / Brinda Kumar -- Desire for Life / Emerson Bowyer -- Proxy Figures / Brinda Kumar -- Layered Realities / Brinda Kumar -- Figuring Flesh / Emerson Bowyer -- Between Life and Art / Brinda Kumar -- Notes -- Works in the Exhibition -- Selected Bibliography -- Index.
"This catalogue is published in conjunction with "Like Life: Sculpture, Color, and the Body (1300-Now)," on view at the Metropolitan Museum of Art, New York, from March 21 through July 22, 2018"--Colophon.
Includes bibliographical references (pages 289-293) and index.
Keywords: Figure sculpture -- Exhibitions; Human figure in art -- Exhibitions; Polychromy -- Exhibitions